Desenvolvimento de nanocompósitos híbridos de epóxi/NTCPM/cargas minerais e avaliação das propriedades mecânicas, elétricas e térmicas - Backes, Eduardo Henrique (2016)
In the present work epoxy/ MWCNT/ mineral fillers nanocomposites were obtained using ultrasonication and calendering. The effect of addition of mineral filler (calcium carbonate, montmorillonite and sepiolite) in electrical, mechanical and thermal properties of epoxy/ MWCNT were analyzed. Two different CNT were studied, with different aspect ration and purity, however only Nanocyl CNT’s presented improvement in the nanocomposites electrical properties and for that reason was employed for hybrid epoxy/ MWCNT/ mineral nanocomposites production. The electrical percolation threshold was determined as 0.04 wt% and for 0.3 wt% the electrical conductivity reached 1.29X10-2 S/m. The addition of calcium carbonate and montmorillonite improved electrical conductivity for epoxy nanocomposites produced with 0.05 wt% CNT and the same behavior was observed for epoxy/ MWCNT / sepiolite nanocomposites at 0.1 wt% CNT. The epoxy/ MWCNT nanocomposite at 0.05% CNT when produzed via calendering presented improvement in the electrical conductivity compared to the same nanocomposite produced via ultrasonication. For epoxy/ MWCNT at 0.05 wt% of CNT, the addition of calcium carbonate in the nanocomposite led to an electrical conductivity 1 decade higher than the epoxy/ 0.05 wt% CNT nanocomposite produced via calendering. The mineral fillers also modified thermal and mechanical behavior of the nanocomposites, and improvements in flexural modulus, thermal stability and Tg were observed.